2017
DOI: 10.1055/s-0037-1615260
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Intravenous Paracetamol for Patent Ductus Arteriosus in Indomethacin-Resistant or Contraindicated Preterm Infants: Three Cases Reports

Abstract: Maintaining the patency of ductus arteriosus (DA) is essential for fetal circulation and normal development of the fetus. In almost-term infants, the DA constricts and causes intraluminal ischemic hypoxia, which eventually leads to the closure and remodeling of the DA a few days after birth. The occurrence of patent DA (PDA) is inversely related to gestational age and weight, with a higher incidence in preterm infants. 1 PDA is a significant cause of morbidity and mortality in preterm infants, including bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In this case series, we confirmed the safety and feasibility of higher-dose intravenous paracetamol (15 mg/kg given every 6 hours for 3 days) for VLBWIs with hsPDA who were indomethacin/ibuprofen-resistant or -contraindicated in Japan, similar to that previously observed in patients with low-dose intravenous paracetamol (7.5 mg/kg, given every 6 hours for 3 days). 13 In our previous study performed using low-dose intravenous paracetamol (7.5 mg/kg given every 6 hours for 3 days), temporary DA closure was observed in two of three (67%) cases with hsPDA and no short-term adverse events occurred during the provision of pharmacological treatment in any cases. However, our protocol of applying low-dose intravenous paracetamol ultimately could not avoid the need for surgical treatment (avoidance rate of surgical ligation: 0%).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this case series, we confirmed the safety and feasibility of higher-dose intravenous paracetamol (15 mg/kg given every 6 hours for 3 days) for VLBWIs with hsPDA who were indomethacin/ibuprofen-resistant or -contraindicated in Japan, similar to that previously observed in patients with low-dose intravenous paracetamol (7.5 mg/kg, given every 6 hours for 3 days). 13 In our previous study performed using low-dose intravenous paracetamol (7.5 mg/kg given every 6 hours for 3 days), temporary DA closure was observed in two of three (67%) cases with hsPDA and no short-term adverse events occurred during the provision of pharmacological treatment in any cases. However, our protocol of applying low-dose intravenous paracetamol ultimately could not avoid the need for surgical treatment (avoidance rate of surgical ligation: 0%).…”
Section: Discussionmentioning
confidence: 69%
“…However, all three infants eventually required surgical closure. 13 This treatment failure was thought to be due to an inadequate dose of paracetamol, given that a higher dose (15 mg/kg, given every 6 hours for 3 days) has been used in most studies, elsewhere in which degree of the efficacy of paracetamol on DA closure was observed. [7][8][9][10][11] Therefore, in the present research, we increased the dose of paracetamol up to 15 mg/kg/dose for evaluation in 16 preterm infants who were indomethacin/ibuprofen-resistant or -contraindicated and examined the safety and feasibility outcomes.…”
mentioning
confidence: 99%
“…Paracetamol at 7.5 mg/kg or 15 mg/kg was administered to PDA patients who were refractory to or contraindicated by existing drug therapies. In this pilot study, three patients were administered 7.5 mg/kg and subsequently required surgical closure, but no adverse events were observed 13. In contrast, 16 patients were administered 15 mg/kg and 9 of them did not require surgery, thereby indicating the drug’s efficacy 14.…”
Section: Introductionmentioning
confidence: 87%
“…In this pilot study, three patients were administered 7.5 mg/kg and subsequently required surgical closure, but no adverse events were observed. 13 In contrast, 16 patients were administered 15 mg/kg and 9 of them did not require surgery, thereby indicating the drug’s efficacy. 14 The neonates who received paracetamol at 15 mg/kg did not present any adverse events as well.…”
Section: Introductionmentioning
confidence: 99%